2019
DOI: 10.1002/jbio.201960025
|View full text |Cite
|
Sign up to set email alerts
|

Bladder tissue characterization using probe‐based Raman spectroscopy: Evaluation of tissue heterogeneity and influence on the model prediction

Abstract: Existing approaches for early-stage bladder tumor diagnosis largely depend on invasive and time-consuming procedures, resulting in hospitalization, bleeding, bladder perforation, infection and other health risks for the patient. The reduction of current risk factors, while maintaining or even improving the diagnostic precision, is an underlying factor in clinical instrumentation research. For example, for clinic surveillance of patients with a history of noninvasive bladder tumors real-time tumor diagnosis can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 64 publications
(82 reference statements)
0
30
0
Order By: Relevance
“…3). The described method has previously been reported in Cordero et al 67 Multivariate curve resolution alternating least squares (MCR-ALS) for collagen distribution of Raman data Initially, the pure components for each biopsy were determined by using an orthogonal projection approach (OPA) algorithm. This function extracts the initial 'pure' components of the set of spectra based on spectral dissimilarity of the data set.…”
Section: Classification Model and Cross-validation Of Raman Datamentioning
confidence: 99%
“…3). The described method has previously been reported in Cordero et al 67 Multivariate curve resolution alternating least squares (MCR-ALS) for collagen distribution of Raman data Initially, the pure components for each biopsy were determined by using an orthogonal projection approach (OPA) algorithm. This function extracts the initial 'pure' components of the set of spectra based on spectral dissimilarity of the data set.…”
Section: Classification Model and Cross-validation Of Raman Datamentioning
confidence: 99%
“…The detection of the drug is consistent with PDT treatment of bladder cancer which induced necrosis. In fact, elevated Raman bands of fibrous proteins in cancer tissues in figure 2 rather point to necrotic tissue than to cancer when compared to another study [10]. 16 additional data sets were collected from eight patients with identical parameters and are expected to give more details about bladder tissue features.…”
Section: Discussionmentioning
confidence: 95%
“…The authors reported that the probe collected mainly signal from deeper tissue layers whereas early changes in the upper urothelial layer were not detected. A recent study collected Raman images from 67 bladder biopsies of 28 patients using a fiber-probe system [10]. After extensive pre-processing to suppress high tissue autofluorescence in Raman spectra, noncancer tissue, low-grade and high-grade cancer were classi-*Corresponding author: C. Krafft: Leibniz IPHT, Albert-Einstein-Str.…”
Section: Introductionmentioning
confidence: 99%
“…Recent technical advancements in compact NIR diode lasers, high‐throughput Raman imaging spectrographs with holographic gratings, deep‐depletion charge‐coupled device (CCD) camera, notch filters/sharp‐edged long‐pass Raman filters and miniaturized fiber‐optic Raman probe designs have permitted the rapid acquisition of NIR tissue Raman spectra in clinical settings [22–24]. Accumulating evidences of NIR Raman spectroscopy for tissue characterization and diagnosis have been reported in a number of organ sites (eg, skin [25–28], breast [29–31], oral cavity [32], larynx/nasopharynx [33–36], esophagus and gastric [37–41], colon [37, 42], lung [11, 43, 44], bladder [45–51], prostate [37, 49, 52], cervix [53, 54], brain [48, 55–58], bone [59, 60], artery [61, 62] etc.). Encouraged by the promising results of ex vivo Raman studies as well as the latest advancement in NIR Raman technologies, substantial progress has been made in translating NIR Raman spectroscopy into real‐time in vivo endoscopic applications.…”
Section: Introductionmentioning
confidence: 99%